Coalescence-induced jumping of in-plane moving droplets: Effects of initial velocity and sideslip angle. (16th January 2023) - Gao, Sihang; Yuan, Zhiping; Wu, Xiaomin
Highlights: Coalescence-induced jumping of in-plane moving droplets is experimentally observed and numerically investigated. Effects of the initial velocity and sideslip angle of the moving droplet on the jumping velocity, energy conversion, and droplet morphology are discussed. The underlying mechanism of the initial velocity and sideslip angle on the coalescence-induced jumping is discussed based on the motion decomposition method. Abstract: Herein, the effects of initial velocity and sideslip angle on the jumping velocity, energy conversion, and morphological evolution of the coalesced droplet were investigated. The results show that the initial velocity and sideslip angle negatively affect the jumping velocity. As the Weber number ( We ) of the moving droplet increases, the main source of the total kinetic energy of the coalesced droplet changes from the released surface energy to the initial kinetic energy of the moving droplet. The initial velocity and sideslip angle cause an asymmetric evolution of the droplet morphology and affect the speed of the coalescence process. Based on the motion decomposition method, the coalescence-induced jumping process comprises two types of coalescence: centripetal coalescence and tangential coalescence. The porportion of the two coalescence types is affected by the We number and sideslip angle, which yields different jumping velocities.